Is the Prevalence of the Pediatric COVID-19 Infection in Oman Underestimated? - Mahmood Dhahir Al-Mendalaw (Oman Medical Journal, 2020)
In May 2020 issue of the Oman Medical Journal, Khamis et al, nicely characterized the epidemiological profiles of the first case series of patients with COVID-19 in Oman.